Development of Sucrose and Citric Acid as the Natural Based Admixture for Fly Ash Based Geopolymer - Kusbiantoro, Andri; Mohd Sobri, Ibrahim; Khairunisa, Muthusamy; Aizat, Alias (2012)
Geopolymer is the state of the art binder in concrete technology. It utilizes alkaline solution to activate alumina and silica precursors from source material and forms aluminosilicate-based binding material. Nevertheless, the presence of high calcium content in the source material can reduce the performance of geopolymer binder, particularly in terms of its workability performance. The available commercial admixture cannot provide significant improvement to the rapid setting time generated by high calcium in geopolymer system. This research studied the effect of sucrose and citric acid as the proposed natural admixture in fly ash based geopolymer binder. Based on Vicat setting time result, these materials behave oppositely in fly ash based geopolymer paste. Sucrose tends to increase the setting time of geopolymer paste, while citric acid has an accelerating effect. An unexpected trend is also shown from the relation between porosity and compressive strength of hardened specimen. It appears that the rapid production of geopolymer gels to fill the water-filled voids was not followed by the quality of gel structure. However, these results have presented an encouraging prospect for natural-based material to be developed as the admixture for geopolymer concrete.